Mandibular angle fracture following closed extraction of lower third molar: A case report and systematic review - Latifi, Fatemeh; Dehghanpour barouj, Mehrdad; Esmaeelinejad, Mohammad (Journal of Dental School, 2018)
<span style="font-size: 9.5pt; mso-bidi-font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-hansi-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; color: #231f20; mso-font-width: 90%;">Objectives Mandibular third molar extraction is among the most commonly performed dental procedures. Fracture of the angle of mandible after third molar extraction is a rare complication of this procedure. Case Herein, we report fracture of the right angle of mandible immediately after extraction of mandibular right third molar in a 38-year old healthy female patient, which was surgically managed. A review of the relevant literature is also presented. Thirty four cases of mandibular fracture following third molar extraction are reported in the literature. Most of these cases were removed surgically. <span style="font-size: 9.5pt; mso-bidi-font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-hansi-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; color: #231f20; mso-font-width: 90%;">Conclusion Systematic review of papers showed that angulation of impacted third molar is one of the most related factors in following fractures of mandibular angle.